2022
DOI: 10.1111/aej.12701
|View full text |Cite
|
Sign up to set email alerts
|

Effect of QMix as final irrigation protocol on periapical healing after single‐visit root canal treatment: A randomised controlled clinical trial

Abstract: The aim of this study was to evaluate radiographic periapical repair after endodontic treatment using QMix or NaOCl irrigation in single‐rooted teeth with apical periodontitis. In this randomised clinical trial, 60 patients were selected and randomised into two groups (n = 30). After instrumentation of root canals, QMix or NaOCl was used as a final irrigation and the canals obturated with gutta‐percha and AH Plus sealer. All the participants were recalled after 12 months and 15 patients were lost to the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…QMix demonstrated a high capability of removing the smear layer and eradicating E. faecalis, high wettability, favorable surface tension properties, and biocompatibility, which, in several reports, demonstrated superior antimicrobial effects when compared in vitro to sodium hypochlorite and chlorhexidine [165 -167]. In a recent randomized clinical trial, however, the use of QMix irrigation solution as a final rinse resulted in no significant difference in periapical healing compared to sodium hypochlorite alone at the end of a one-year follow-up period [168].…”
Section: Qmixmentioning
confidence: 99%
“…QMix demonstrated a high capability of removing the smear layer and eradicating E. faecalis, high wettability, favorable surface tension properties, and biocompatibility, which, in several reports, demonstrated superior antimicrobial effects when compared in vitro to sodium hypochlorite and chlorhexidine [165 -167]. In a recent randomized clinical trial, however, the use of QMix irrigation solution as a final rinse resulted in no significant difference in periapical healing compared to sodium hypochlorite alone at the end of a one-year follow-up period [168].…”
Section: Qmixmentioning
confidence: 99%
“…Interestingly, clinical studies comparing combined irrigants did not report statistically significant differences in reducing bacterial counts (Ballal, Gandhi, et al, 2019;Ballal, Jain, et al, 2019;Malkhassian et al, 2009), unless Tandon et al (2022). Also, in a recent clinical study (Sapmaz et al, 2023), QMix was found inferior to NaOCl irrigation in single-rooted teeth with apical periodontitis in terms of periapical healing after singlevisit root canal treatment.…”
Section: Introductionmentioning
confidence: 97%
“…Although several in vitro studies investigated these combined irrigants' biocompatibility, and antimicrobial and smear layer removal properties (Ballal et al, 2023; Ballal, Jain, et al, 2019; Johal et al, 2007; Torabinejad, Cho, et al, 2003; Torabinejad, Khademi, et al, 2003; Torabinejad, Shabahang, et al, 2003), very few clinical studies have been conducted with these irrigants (Ballal, Gandhi, et al, 2019; Malkhassian et al, 2009; Sapmaz et al, 2023; Torabinejad et al, 2005). Interestingly, clinical studies comparing combined irrigants did not report statistically significant differences in reducing bacterial counts (Ballal, Gandhi, et al, 2019; Ballal, Jain, et al, 2019; Malkhassian et al, 2009), unless Tandon et al (2022).…”
Section: Introductionmentioning
confidence: 99%